THE EFFECT OF AMD ON THE MODAL PARAMETERS OF THE REINFORCED CONCRETE BUILDING BY FINITE ELEMENT METHOD (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Earthquake engineers have taken many precautions in their building designs to protect and minimize destructive effects. In this way, many new design and reinforcement methods have been developed against seismic loads. The use of an active mass damper (AMD) is one of the developed methods. One of the most important negative aspects of the use of AMD is the increase in the structural period. Therefore, in this study, the effects of AMD on periods and mode shapes in symmetrically reinforced concrete building model were investigated. For this, two models with and without AMD were created by the finite element method and modal parameters were compared. As a result of the data obtained, it has been observed that the RC building model makes more balanced displacements, as can be understood from the mode shapes, without increasing the period of the RC building to a dangerous level. It is known that AMD reduces the seismic effect by acting in the opposite direction to the seismic effect on the structure. Active mass damper can be used in reinforced concrete buildings, provided that it does not increase period too much.